The Trophic relationships in the Water System of the Province of Rivers: Ichthyoelephas humeralis and Brycon alburnus (Revista Científica Ciencias Naturales y Ambientales, 2012)
The stomach contents of 245 specimen Ichthyoelephas humeralis and 230 of Brycon alburnus were analyzed for determination of feeding habits and trophic relationships in Los Rios province hydric system, between march and december, 2010. The Relative importance index was used, based in the numeric method, weight and occurrence frequency, also obtaining trophic niche breadth index of Levin and overlapping index of Morisita. I. humeralis was determinated as a detritivorousphytophagousfish, feeding from 7 food groups, being the most important of them the detritus and microalgae. B. alburnus was determinated as an omnivorous fish; the predominant food components were mixed plant material, fish and insects. The trophic niche breadth determinated to I. humeralis (Bi=0.06) and B. alburnus (Bi=0.09) as selective predators, feeding of ahigher percentage of few species. Comparing both species by trophic overlapping index, a middle overlapping (Cλ 0.47) was obtained, and indicated that both species share the same space because they feed some similar preys but in different proportions.
Keywords: trophic relationships; Ichthyoelephas humeralis; Brycon alburnus; detritivorous; phytophagous; omnivorous